Análise objetiva de lesões cervicais não cariosas através de escaneamento digital tridimensional - Charamba, Caroline de Farias (2021)
To explore the use of 3D intraoral scanner/image analysis for the detection and monitoring of simulated non-carious cervical lesions (NCCLs) in vitro. A total of 288 NCCLs of different severities and simulated using a laboratorial model associating toothbrush stiffness (soft, medium and hard) and toothpaste abrasivity (low, medium, high and negative control) were analyzed. Dental impressions were taken from specimens before and after 35K and 65K brushing strokes, and then scanned with a CEREC Omnicam scanner. 3D models were analyzed for volumetric tooth loss. 3D optical profilometry was considered as gold-standard. Data were analyzed using ANOVA and Fisher’s PLSD tests (alpha=0.05), and agreement between methods by using intraclass correlation coefficient. Toothbrushes of hard and mid stiffness caused higher tooth loss than soft when associated with the highest abrasive, at 35K and 65K strokes (p<0.001). Variation in slurry abrasivity led to differences in tooth loss (with control<low<medium<high, p<0.0001) after both 35K and 65K strokes, regardless of the type of toothbrush used, except at 35K, wherein control=low (p=0.55). 35K strokes caused less tooth loss than 65K for all abrasive slurries (p<0.0001) except controls. The intra-class correlation coefficient for agreement between the test and gold-standard methods was 0.85. Analysis of 3D images from intraoral scanner could detect and monitor NCCLs progression, although this ability was limited on incipient lesions. Overall good agreement was found between the test method and optical profilometry. The suggested method may be applicable to detect and monitor NCCLs clinically.